Erratum to accidental invisible intrathoracic disseminated pT4-M1a: a distinct lung cancer with favorable prognosis - Team, Editorial (Journal of Thoracic Disease, 2015)
The note of “Accidental disseminated disease” for Figure 2C was missing in the article appeared on Page 1205-1212 (1) of the July 2015 Issue of the Journal of Thoracic Disease (JTD)